Combined endoscopic and transcutaneous approach for immobile parotid stones. (January 2014) - Mikolajczak, Stefanie; Bremke, Martin; Beutner, Dirk; Luers, Jan Christoffer
Abstract Conclusion: Salivary stones in the parotid gland that are not amenable to endoscopic extraction can safely be removed by a combined, endoscopic-external approach. Objective: Limitations for endoscopic removability of salivary stones from the parotid gland are immobile stones in the deeper salivary duct system. A combined endoscopic and transcutaneous approach gives access to these stones with possible preservation of the parotid gland. Methods: A total of 10 consecutive patients were treated using the combined approach for the management of sialolithiasis of the parotid gland. The patients had previously undergone a sialendoscopy under local anesthesia and were proven to have large, immobile salivary stones in the salivary duct. Results: In all patients, the procedure was successfully conducted with extraction of impacted stones. In 60% of the patients, a temporary stenting of the salivary duct was performed. All patients showed good clinical results with restored drainage of the salivary duct system and preserved gland function.